ORGANIZATIONAL AND ECONOMIC MECHANISM OF DEVELOPMENT OF PUBLIC FOOD ENTERPRISES UNDER FRANCHISING AND CLUSTER APPROACH (Marketing Journal, 2025)
This study is devoted to developing an organizational and economic mechanism aimed at improving efficiency in the public catering (HoReCa) sector through the integration of franchising and cluster approaches. Within this framework, vertical (franchise chai n) and horizontal (cluster synergy) integration among network entities are viewed as a coordinated system that ensures economic stability, innovative activity, and regional growth. The conceptual foundation of the mechanism is based on the following theore tical paradigms: the Resource -Based View (RBV), knowledge transfer and replication strategies, agglomeration and cluster economies, and the evolutionary model of Multi -Unit Franchising. Based on these theoretical approaches, the integration of franchising and cluster models is interpreted as a mechanism that accelerates the innovative development of the network.
Keywords: franchising; cluster approach; agglomeration; organizational - economic mechanism; RBV; multi -unit franchising; knowledge transfer